2017
DOI: 10.1186/s12903-017-0357-6
|View full text |Cite
|
Sign up to set email alerts
|

Release kinetics and mitogenic capacity of collagen barrier membranes supplemented with secretome of activated platelets - the in vitro response of fibroblasts of the periodontal ligament and the gingiva

Abstract: BackgroundPlatelet preparations can stimulate the healing process and have mitogenic properties. We hypothesized that collagen barrier membranes (CBM), clinically used in guided bone regeneration and guided tissue regeneration, can serve as carriers for platelet secretome.MethodsSecretome was generated from washed platelets and unwashed platelets (washed/unwashed PSEC) and lyophilized onto CBM. Overall appearance of CBM was evaluated by scanning electron microscopy. The impact of PSEC on cell attachment was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Both soft tissue wound-healing and bone regeneration are initiated by the formation of a fibrin clot. In the clots, activated platelets release a myriad of growth factors and cytokines/chemokines that stimulate the migration and proliferation of repair cells [ 20 , 21 ]. Among these factors are transforming growth factor-β1 (TGF-β1) and various isoforms of platelet-derived growth factor (PDGF).…”
Section: Introductionmentioning
confidence: 99%
“…Both soft tissue wound-healing and bone regeneration are initiated by the formation of a fibrin clot. In the clots, activated platelets release a myriad of growth factors and cytokines/chemokines that stimulate the migration and proliferation of repair cells [ 20 , 21 ]. Among these factors are transforming growth factor-β1 (TGF-β1) and various isoforms of platelet-derived growth factor (PDGF).…”
Section: Introductionmentioning
confidence: 99%
“…We made the choice to coat the vCM with either enamel matrix derivative (EMD), which is widely used in periodontal regenerative surgery, or one of the following recombinant growth factors TGF-β1, PDGF-BB, FGF-2, or GDF-5 for a short, clinically relevant 10-min period. Our choice was partially based on the assumption that the majority of the listed proteins are released by activated platelets, and are thus naturally present in the blood clot [ 46 , 47 ]. Our results have shown that the vCM adsorbed each of the four growth factors with an efficiency higher than 93% ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, our results of strongly induced SERPINE1 gene expression in primary hPDLCs, hOFs, and HUVECs grown on native as well as TGF-β1-, PDGF-BB- or FGF-2-coated vCMs strongly support the favorable effect of vCM on the regenerative process. The three growth factors TGF-β1, PDGF-BB, and FGF-2 as well as the investigated by us thrombospondin 1, encoded by the THBS1 gene in humans, are released by activated platelets at wounded sites [ 46 , 47 , 58 ]. All four factors are known to efficiently bind extracellular matrix proteins such as collagen [ 7 , 59 ] and thus, they may coat the vCM in situ after its placement at the defect site.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Mozgan E.M. et al [91], secretome of washed platelets (washed PSEC) and secretome of unwashed platelet preparations (unwashed PSEC) were lyophilized onto CBM. Supernatants were collected by adding and replacing medium after 1 to 48 h. Mitogenic response of human periodontal fibroblasts was induced by the supernatants and showed the highest levels of total protein, TGFβ1, and PDGF-BB in the first hour.…”
Section: Platelet Secretome (Psec)mentioning
confidence: 99%